Estimation of Serum Levels of Testosterone and Estrogen in Vitiligo Patients - Sherief Mahdy Hussein (Journal of Global Pharma Technology, 2016)
Vitiligo is an idiopathic systemic autoimmune disorder affecting skin, hair and oral mucosa. This genetic moreover acquired disease distinguished by melanin absence causes morbidity over all races. Although thyroid disorder has been known as a key trigger of this pathology, arange of other factors plays serious role in its presentation. Several hormones such as, testosterone and estrogen have been suspected as drivers of this disorder. The present study aimed to determine the levels oftestosterone, estrogen and the ratio of testosterone/ estrogen in serum of patients with vitiligo compared to matches control group .The study included50 patients from Egyptian population with lesions of generalized vitiligo (29 males and 21 females; median age 35.0 years; range 28–40 years and 50 healthy volunteers as control group (22 males and 28 females; median age 36.1 years; range 25–40years). All patients of vitiligo were recruited from Medical research center of excellence of National Research Centre, Egypt, during a period of 4 months (February 2019 to May 2019). The mean duration of the disease in the vitiligo group was 5.00years.Vitiligo diagnosis is based on if areas of patient's skin, hair or eyes lose coloring and confirmation is done using Wood’s lamp. Blood samples were obtained from both the patient and control groups, testosterone, estrogen and the ratio of testosterone/ estrogen. Results: The present results declared significant elevation of testosterone (+144.5), estrogen (+116.048) as well as testosterone/ estrogen ratio compared to control subjects. Conclusion: Some endocrine markers play a principle role in pathogenesis and/or consequences of vitiligo. The abnormally disturbed levels of these markers lead to melanocyte damage and/or depigmentation.Keywords: Autoimmune disease, Melanin loss, Oxidative stress, Vitiligo, Estrogen, Testosterone, Testosterone /Estrogen ratio.